Two new species of the long-jawed orb-weaving spider genus Pachygnatha Sundevall, 1823 (Araneae, Tetragnathidae) from southern China - Huang, Zongguang; Wu, Yecheng; Yin, Haiqiang; Xu, Xiang; Chen, Junhao (Zootaxa, 2024)
The spider genus Pachygnatha Sundevall, 1823 is widely distributed in the world, exhibiting higher species diversity in Palaearctic and Nearctic regions. Two new Pachygnatha species from southern China are described based on males and females: Pachygnatha shengtangensis sp. nov. and Pachygnatha unciniformis sp. nov. Detailed descriptions, color photographs and line drawings of the two new species, and a distribution map of Chinese Pachygnatha are provided. Furthermore, the COI sequences of the new species, and the p-distances are also presented between seven Pachygnatha species including five known and the two new species. The embolic medial groove, previously recorded and described in the genus Glenognatha Simon, 1887, is also present in the two new species, representing the first record of this structure in the genus Pachygnatha.